Answer:
y = - 4x + 13
Step-by-step explanation:
In order to do this problem you would need a whole new equation, but you will use what is given to you:
instead of going with:
x - 4y = 20
Turn it into y = mx + b form, also known as slope-intercept form:
x - 4y = 20
-x = -x
_________
- 4y = 20 - x
Then divide both sides by - 4:
![\frac{-4y}{-4} = \frac{-x + 20}{-4}](https://tex.z-dn.net/?f=%5Cfrac%7B-4y%7D%7B-4%7D%20%3D%20%5Cfrac%7B-x%20%2B%2020%7D%7B-4%7D)
You will then get:
y = ![\frac{1}{4}x - 5](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7Dx%20-%205)
From this equation we will only need the slope!
m || = ![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
(This slope is for parallel)
but if you want perpendicular to the slope, then we need the negative reciprocal!
Negative reciprocal is a flipped version of the value that is negative, for example:
2 = ![-\frac{1}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B2%7D)
Because
= 2
Now we will find the perpendicular slope which is:
m ⊥ = - 4
Now substitute this slope into slope intercept form:
y = mx + b
(-3) = -4(4) + b
(Take away parentheses)
-3 = -16 + b
(Move - 3 to the other side, by making it positive, but what you do to one side, you do to the other)
= -13 + 6
(Move - 13 to the other side, by make - 13 into +13)
+13 = +13
________
13 = b
(This is you b, also known as you intercept)
Your answer is:
y = -4x + 13